Речовий скарб літописного Губина - Винокур, І.С.; Якубовський, В.І.; Журко, О.І.; Мегей, В.П. (Археологія, 2003)
Статтю присвячено публікації матеріалів речового скарбу жіночих прикрас із городища Губина — літописного міста Болохівської землі XII—XІІІ cm. В статье описаны ювелирные изделия из вещевого клада XII - XIІІ в., которые происходят из городища летописного Губина — города Болоховской земли. В составе клада - два набора (гарнитура) женских украшений: серебряные килты, браслеты, кольца, перстни, сережки киевского типа, полуторавитковые височные подвески, каменный нательный крестик — всего 40 вещей. Вещи клада свидетельствуют о развитии ювелирного дела в Болоховской земле XII - XIІІ в., которое продолжило киевские и черниговские традиции ювелирного производства, а также вобрало в себя влияние ювелирного искусства Галицко-Волынского княжества. The jewelry from the storage treasure trove dating from the 12th to the 13th centuries are described in the article. It was found on the territory of the hillford of the annalistic Hubyn, the town of the Bolokhiv land. It consists of two sets of the female jewelry: the silver pendants (kolty), the bracelets, the signet-rings, the rings, the ear-rings of Kiev type, one and a half coils temporal pendants, worn next to the skin stone cross. On the whole, it includes 40 things. The things of this treasure trove testify to the development of the jewelry art of Bolokhiv land in the 12th—13th centuries, which has continued Kyiv and Chemigiv traditions of the jewelry production and has absiorbed the influence of the jewelry art of the Halytsian and Volinian principality as well.